Perception, Attitude, and Confidence of Physicians About Antimicrobial Resistance and Antimicrobial Prescribing Among COVID-19 Patients: A Cross-Sectional Study From Punjab, Pakistan - Hayat, Khezar; Mustafa, Zia Ul; Ikram, Muhammad Nabeel; Ijaz-Ul-Haq, Muhammad; Noor, Irum; Rasool, Muhammad Fawad; Ishaq, Hafiz Muhammad; Rehman, Anees Ur; Hasan, Syed Shahzad; Fang, Yu (Frontiers in Pharmacology, 2022)
Background: Patients with coronavirus disease 2019 (COVID-19) could experience multiple coinfections, and judicial antimicrobials, including antibiotics, is paramount to treat these coinfections. This study evaluated physicians' insights about antimicrobial resistance (AMR) and antimicrobial prescribing in patients with COVID-19. Methods: A self-administered and validated online questionnaire was disseminated among physicians working in public sector hospitals in Punjab, Pakistan, from April to May 2021. The study also assessed the validity and reliability of the study questionnaire using exploratory factor analysis and Cronbach’s alpha. In addition, the descriptive and inferential statistics present survey results. Results: A total of 387 physicians participated in this study. The study showed that the questionnaire demonstrated good internal consistency (Cronbach’s alpha=0.77). Most physicians (n=221, 57.1%) believed that AMR is a considerable problem in Pakistan. Less than a quarter of respondents (n=91, 23.5%) consulted with local antibiotic resistance data to prescribe antibiotics in COVID-19 patients. However, the respondents were confident to select a suitable antibiotic (n=229, 59.2%). More than three-quarters of the respondents believed that advice from a senior colleague (n=336, 86.8%), infectious disease (ID) physician (n=315, 81.4%), and implementing antimicrobial stewardship programs (ASPs) could facilitate appropriate prescribing of antibiotics in COVID-19 patients. Multivariate logistic regression revealed that physicians with more than 10 years of experience had higher odds of consulting local guidelines for antibiotic therapy (OR, 4.71 95% CI: 1.62-13.73, p=0.004) than physicians with less than 5 years of experience. Similar trends were found for consulting national guidelines and local resistance data to select an empiric antibiotic therapy. Conclusions: AMR-related awareness was optimal among physicians. Only a few physicians looked up local antibiotic resistance data before prescribing antibiotics to COVID-19 patients empirically. The significant approaches advised by physicians to reduce AMR risk among COVID-19 patients were the implementation of ASPs combined with advice from ID physicians.